2019
DOI: 10.35699/1981-3171.2019.13553
|View full text |Cite
|
Sign up to set email alerts
|

Práticas de Lazer do Povo Indígena Tremembé

Abstract: Verifica, descreve e traça um perfil, através do método etnográfico, das práticas de lazer do povo indígena Tremembé de Almofala, no município de Itarema, estado do Ceará. Para a coleta dos dados utilizaram-se entrevistas estruturadas, relatos, fotos e vídeos, abrangendo 78 pessoas de 04 a 87 anos, indígenas residentes na praia de Almofala. Através da análise dos dados foi apontado como principais resultados o perfil, a singularidade e a descrição do lazer, bem como traços da cultura inseridos nesse processo; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
4
0
4
Order By: Relevance
“…The present study investigated the Tremembé Indigenous people, who inhabit the district of Almofala, in the municipality of Itarema, one of the 12 hamlets present in the Northeastern state of Ceará 23 . The municipality of Itarema had an estimated population for 2021 of 42,595 people 24 .…”
Section: Methodological Pathmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study investigated the Tremembé Indigenous people, who inhabit the district of Almofala, in the municipality of Itarema, one of the 12 hamlets present in the Northeastern state of Ceará 23 . The municipality of Itarema had an estimated population for 2021 of 42,595 people 24 .…”
Section: Methodological Pathmentioning
confidence: 99%
“…Finally, a qualitative study conducted with the Tremembé people from Almofala showed that many leisure activities are practiced in the natural environment, as well as children's plays with animals. Such activities foster the feeling of belonging to a group 23 and favor collective educational actions.…”
Section: Focus On Clinical Care To the Detriment Of Educational Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Este estudo foi desenvolvido no povo indígena de Tremembé, com território localizado no distrito de Almofala, município de Itarema, que integra as 12 aldeias distribuídas no estado do Ceará 23 . O município de Itarema possui uma população estimada para 2021 de 42.595 pessoas 24 .…”
Section: Percurso Metodológicounclassified